2002
DOI: 10.1080/0963748021000044769
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant effect ofβ-carotene on lipid peroxidation and synergism with tocopherol in an emulsified linoleic acid model system

Abstract: The antioxidant effect of beta-carotene was investigated in an emulsified linoleic acid model system with or without exposure to light. The effect of tocopherol on the antioxidant action of beta-carotene was also investigated. The antioxidant effect of beta-carotene was significant, and synergistically increased by the addition of rac alpha-tocopherol, in the dark but not in the light. It was#10; confirmed that superoxide anions (O(2)(-)) and hydrogen peroxide (H(2)O(2)) were formed during the light exposure, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 8 publications
0
5
0
2
Order By: Relevance
“…Similarly, β ‐carotene contributes to the meat preservation against oxidation by quenching reactive oxygen species and retarding lipid and protein oxidation . It has been shown that β ‐carotene acts synergistically with α ‐tocopherol with respect to avoiding lipid peroxidation . The higher anti‐oxidant contents can be particularly beneficial for extending the shelf life of organic beef as a result of its higher concentration of easily oxidizable n‐3 PUFA …”
Section: Resultsmentioning
confidence: 99%
“…Similarly, β ‐carotene contributes to the meat preservation against oxidation by quenching reactive oxygen species and retarding lipid and protein oxidation . It has been shown that β ‐carotene acts synergistically with α ‐tocopherol with respect to avoiding lipid peroxidation . The higher anti‐oxidant contents can be particularly beneficial for extending the shelf life of organic beef as a result of its higher concentration of easily oxidizable n‐3 PUFA …”
Section: Resultsmentioning
confidence: 99%
“…When linoleic acid is oxidized in an emulsified model system, types of radicals present in the oxidation process can be varied depending on the light/dark conditions [29]. It is known that superoxide anion (O 2 À ) and hydrogen peroxide are formed during the light exposure, and hydroxyl radicals ( S OH) are generated according to Haber-Weiss reaction [30].…”
Section: Discussionmentioning
confidence: 99%
“…The assay principle has been described in the literature [15]. Briefly, 0.5 g b-carotene was dissolved in 1 ml of chloroform and mixed with 6.25 ll of linoleic acid and 25 ll of Tween-20.…”
Section: B-carotene Linoleic Acid Bleaching Testmentioning
confidence: 99%